Great pajama jobs : your complete guide to working from home - Hannon, Kerry (John Wiley & Sons, Inc., 2020)
"Many people spend hours a week commuting into work. Some arrive to an office that is uninspiring or chaotic and wonder, "Why did I come in at all?" They spend all day answering emails and fiddling with computer systems, which they could easily do from home. Home Sweet Home Office is the guide to finding a job where you can ditch the commute and stuffy office environment and work remotely. Career expert Kerry Hannon walks you through getting a remote-access job and thriving remotely, featuring interviews with professionals who have done so themselves. Hannon also profiles companies who are known for remote-access employment opportunities"--